Engaging practitioners as co-researchers in national policy evaluations as resistance to patriarchal constructions of expertise: The case of the end of year three evaluation of the access and inclusion model - Sheridan, Denise; Robinson, Deborah; Codina, Geraldene; Gowers, Sofia J.; O’Sullivan, Lisha; Ring, Emer (Frontiers in Education, 2022)
This paper draws on feminist theory to argue that the engagement of Early Learning and Care (ELC) practitioners as co-researchers in the evaluation of national policies may offer opportunities for identity shift in a workforce that is largely female. Such approaches are counter-hegemonic since they enact resistances to patriarchal, top-down conceptualizations of what it means to be an 'expert’. These arguments are explored in the context of the end-of-three-year evaluation of Ireland's Access and Inclusion Model (AIM). The Department of Childhood, Equality, Disability, Integration, and Youth (DCEDIY) commissioned the evaluation to cast light on AIM's effectiveness in ensuring the full inclusion and meaningful participation of children with disabilities in a government-subsidized program of pre-schooling known as the Early Childhood Care and Education (ECCE) program. Its methodology included the appointment of seventeen Practitioner Researchers (PRs) as co-researchers who constructed case studies of how AIM is used in settings, and what its impacts are. Central to the paper is a critical reflection written by one co-researcher (who is also the lead author) which explores her gendered experience of co-researching, and its transformative impact on her identity, agency, knowledge, and practice. The paper ends with a call for more participative approaches to the evaluation of national policies through the engagement of practitioners as researchers. It is argued that this would result in evaluations that were more attuned to the vernacular of practice, and hence more impactful. It also offers opportunities for professional development whilst symbolizing the validation of practitioner expertise by policy makers in a sector where low pay and low status have long been issues of concern.